Spinal cord compression due to carcinoid metastasis. - Gray, J. A. (BMJ Group, 1988)
A case of cord compression secondary to the carcinoid syndrome is reported. The patient made an excellent response to surgical treatment, emphasizing that active management of this unusual complication should be considered.